2017
DOI: 10.1186/s12985-017-0715-7
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus and cytomegalovirus infections and their clinical relevance in Egyptian leukemic pediatric patients

Abstract: BackgroundEpstein-Barr virus (EBV) and human cytomegalovirus (CMV) infections are environmental risk factors affecting the outcome of cancer due to an impairment in the cell-mediated immunity. Therefore, this study aimed to detect the frequency of EBV and CMV DNA and their association with clinical characteristics and outcome of pediatric leukemic patients.MethodsSamples of 50 immunocompromised pediatric leukemic patients and 30 apparently healthy children were subjected to the amplification of EBV DNA by one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
5
10
1
1
Order By: Relevance
“…Hospitalization itself is a form of stress, which in turn could stimulate reactivation of herpesviruses including EBV (23). A strong relation was found in a study between cytomegalovirus super-infection and EBV reactivation leading the authors to suggest that cytomegalovirus might be an important co-factor in EBV pathogenesis, especially in immunocompromised patients (24). There were 3 cases of malaria infection preceding reactivation of EBV in our study.…”
Section: Discussionmentioning
confidence: 54%
“…Hospitalization itself is a form of stress, which in turn could stimulate reactivation of herpesviruses including EBV (23). A strong relation was found in a study between cytomegalovirus super-infection and EBV reactivation leading the authors to suggest that cytomegalovirus might be an important co-factor in EBV pathogenesis, especially in immunocompromised patients (24). There were 3 cases of malaria infection preceding reactivation of EBV in our study.…”
Section: Discussionmentioning
confidence: 54%
“…Then, qualitative PCR assay was performed according to the previously published protocols. [25][26][27][28] Quantitative Real-Time PCR HPV, EBV, and HMTV viral loads were measured in fresh tissues by a quantitative real-time detection system (Applied Biosystems 7500 Fast Real-Time PCR system Thermal Cycling Block, USA). The amplification was conducted in a final volume of 25 μL containing 1X Qiagen Sybrgreen ® PCR Master Mix kit (Qiagen, Valencia, USA), 0.2 μM of each forward and reverse primer for each virus, and 100ng of extracted DNA.…”
Section: Molecular Detection Of Viral Dnasmentioning
confidence: 99%
“…Another study detected EBV and CMV coinfection in pediatric patients with leukemia. The researchers noted a borderline association with worse overall survival, indicating that EBV and CMV infections may act upon the prognosis and the survival rates of these patients [ 62 ]. In HIV-1 seropositive patients from India, Patekar et al (2015) [ 63 ] ascertained that patients with high antibody titers against EBV/CMV exhibited the lower T cell CD4+ counts (less than 200 cells/mm 3 ).…”
Section: Clinical Manifestations Of CMV and Ebv Infectionsmentioning
confidence: 99%
“…Loutfy et al (2017) [ 62 ] found EBV or CMV DNA in 56% of pediatric patients with leukemia, who showed an EBV/CMV coinfection rate of 18%. Nevertheless, as the number of EBV/CMV coinfected patients was small, no statistical association between coinfection and leukemia severity was found.…”
Section: Prevalence Of CMV and Ebv Infections In Patients With Hemmentioning
confidence: 99%